Contextual factors associated with cancer screening uptake: A systematic review of observational studies - Rollet, Quentin; Tron, Laure; De Mil, Rémy; Launoy, Guy; Guillaume, Élodie (Preventive medicine, 2021)
We conducted a systematic review of a wide range of contextual factors related to cancer screening uptake that have been studied so far. Studies were identified through PubMed and Web of Science databases. An operational definition of context was proposed, considering as contextual factors: social relations directly aimed at cancer screening, health care provider and facility characteristics, geographical/accessibility measures and aggregated measures at supra-individual level. We included 70 publications on breast, cervical and/or colorectal cancer screening from 42 countries, covering a data period of 24 years. A wide diversity of factors has been investigated in the literature so far. While several of them, as well as many interactions, were robustly associated with screening uptake (family, friends or provider recommendation, provider sex and experience, area-based socio-economic status…), others showed less consistency (ethnicity, urbanicity, travel time, healthcare density …). Screening inequities were not fully explained through adjustment for individual and contextual factors. Context, in its diversity, influences individual screening uptake and lots of contextual inequities in screening are commonly shared worldwide. However, there is a lack of frameworks, standards and definitions that are needed to better understand what context is, how it could modify individual behaviour and the ways of measuring and modifying it. •This review includes 70 studies from 42 countries, covering a data period of 24 years.•The context in which people evolve partially determines individual cancer screening uptake.•Context literature suffers multiple limitations needing more attention.•There is a need for more theoretical and operational development to better understand contextual effects.